THE IMPACT OF THE COMPETITIVE ENVIRONMENT ON LIGHT INDUSTRY ENTERPRISES - Saidmuradova T. S.; Quromboyeva N. Q. (Bright Mind Publishing, 2025)
This article presents the current problems encountered in the activities of enterprises and organizations in our country, the competitive environment of production in domestic and foreign markets, the five-component model of competition for industry structure and its analysis, internal competition in one industry, conducting strong competitive struggle, and high barriers to entry into the market.
Keywords: Competition, marketing, competitive environment, internal and external competition, export potential, five component model of competition.